YAP1 alleviates sepsis-induced acute lung injury via inhibiting ferritinophagy-mediated ferroptosis - Zhang, Jing; Zheng, Yongping; Wang, Yun; Wang, Jin; Sang, Aming; Song, Xuemin; Li, Xinyi (Frontiers in Immunology, 2022)
Ferroptosis is a phospholipid peroxidation-mediated and iron-dependent cell death form, involved in sepsis-induced organ injury and other lung diseases. Yes-associated protein 1 (YAP1), a key regulator of the Hippo signaling pathway, could target multiple ferroptosis regulators. Herein, this study aimed to explore the involvement of ferroptosis in the etiopathogenesis of sepsis-induced acute lung injury (ALI) and demonstrate that YAP1 could disrupt ferritinophagy and moderate sepsis-induced ALI. Cecal ligation and puncture (CLP) models were constructed in wild-type (WT) and pulmonary epithelium-conditional knockout (YAP1f/f) mice to induce ALI, while MLE-12 cells with or without YAP1 overexpression were stimulated by lipopolysaccharide (LPS) in vitro. In-vivo modes showed that YAP1 knockout aggravated CLP-induced ALI and also accelerated pulmonary ferroptosis, as presented by the downregulated expression of GPX4, FTH1, and SLC7A11, along with the upregulated expression of SFXN1 and NCOA4. Transcriptome research identified these key genes and ferroptosis pathways involved in sepsis-induced ALI. In-vitro modes consistently verified that YAP1 deficiency boosted the ferrous iron accumulation and mitochondrial dysfunction in response to LPS. Furthermore, the co-IP assay revealed that YAP1 overexpression could prevent the degradation of ferritin to a mass of Fe2+ (ferritinophagy) via disrupting the NCOA4–FTH1 interaction, which blocked the transport of cytoplasmic Fe2+ into the mitochondria via the mitochondrial membrane protein (SFXN1), further reducing the generation of mitochondrial ROS. Therefore, these findings revealed that YAP1 could inhibit ferroptosis in a ferritinophagy-mediated manner, thus alleviating sepsis-induced ALI, which may provide a new approach to the therapeutic orientation for sepsis-induced ALI.